2016
DOI: 10.1016/j.ophtha.2016.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Rectus Extraocular Muscle Size and Pulley Location in Concomitant and Pattern Exotropia

Abstract: Purpose To determine if rectus extraocular muscle (EOM) sizes and pulley locations contribute to exotropia, we used magnetic resonance imaging (MRI) to measure these factors in normal control subjects, and subjects with concomitant and pattern exotropia. Design Prospective, case control study. Participants Nine subjects with concomitant exotropia, 6 patients with pattern exotropia, and 21 orthotropic normal controls. Methods High-resolution, surface coil MRI was obtained in contiguous, quasi-coronal plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
(36 reference statements)
1
13
0
Order By: Relevance
“…A subsequent MRI study showed that these pulleys could be mislocated in some patients with pattern strabismus (Clark et al 1998). A more recent MRI study showed that rectus muscle pulleys are misplaced in human subjects with pattern exotropia, but not in patients with concomitant exotropia (Hao et al 2016). Another recent MRI study showed that rectus muscle pulleys can also be misplaced in patients with superior oblique palsy (Suh et al 2016).…”
Section: Abnormalities Of Eye Muscles and Orbital Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent MRI study showed that these pulleys could be mislocated in some patients with pattern strabismus (Clark et al 1998). A more recent MRI study showed that rectus muscle pulleys are misplaced in human subjects with pattern exotropia, but not in patients with concomitant exotropia (Hao et al 2016). Another recent MRI study showed that rectus muscle pulleys can also be misplaced in patients with superior oblique palsy (Suh et al 2016).…”
Section: Abnormalities Of Eye Muscles and Orbital Tissuesmentioning
confidence: 99%
“…As noted early in this review, pattern strabismus is often clinically described in terms of oblique muscle dysfunction. MRI studies of rectus muscle pulleys (Hao et al 2016; demonstrate that other peripheral factors can contribute to incomitance. However, the neurophysiological evidence discussed above indicates that pattern strabismus is also associated with fundamental abnormalities in the neural signals controlling eye movement.…”
Section: Future Directionsmentioning
confidence: 99%
“…It is debated whether incomitant strabismus patterns are due to orbital mechanical forces, such as oblique muscle dysfunction, altered rectus muscle action, or displaced pulleys (Ghasia and Shaikh 2013;Ghasia et al 2015;Hao et al 2016;Kushner 2010;Narasimhan et al 2007;Oh et al 2002). The surgery performed to induce strabismus in monkeys 2 and 3 caused changes in eye muscle mechanics that contributed to the incomitance of their ocular deviation.…”
Section: Discussionmentioning
confidence: 99%
“…MRI of the orbits without and with contrast is preferred [67] if ophthalmoplegia is felt to be related to a primary disease process within the orbit affecting the extraocular muscles or if there is history of trauma, enophthalmos, proptosis, orbital inflammation, or chemosis. An MRI of the orbits with the globes imaged during different gaze positions may aid in identifying a potential muscular slip or pulley abnormality [68].…”
Section: Mrimentioning
confidence: 99%